Occurrence of Aspergillus species and aflatoxin contamination in raw and roasted peanuts from formal and informal markets in Eldoret and Kericho towns, Kenya - Nyirahakizimana, H.; Mwamburi, L.; Wakhisi, J.; Mutegi, C.; Christie, M.E.; Wagacha, M. (Scientific Research Publishing, Inc., 2013)
The population and diversity of fungal species and levels of aflatoxin contamination were investigated in 228 marketed peanut samples; 140 from formal and 88 from informal markets, in Kericho and Eldoret towns of Kenya. Ground pea- nut samples were cultured on Modified Dichloran Rose Bengal (MDRB) agar while aflatoxin level was quantified based on indirect competitive ELISA. Correlation between the incidence of major aflatoxin-producing fungal species and aflatoxin levels was also established. Fungal species commonly isolated from the peanut samples included Asper-gillus flavus L strain, A. flavus S strain, A. parasiticus, A. tamarii, A. caelatus, A. alliaceus (all of Aspergillus section Flavi) and A. niger. Fungi isolated in low frequency included Fusarium spp., Penicillium spp., Mucor spp. and Rhi- zopus spp. Aflatoxin levels in peanut products ranged from 0 to 2345 μg/kg in raw peanuts, 0 to 382 μg/kg in roasted coated peanuts, and 0 to 201 μg/kg in roasted de-coated peanuts. Overall, levels of total aflatoxin were higher in sam- ples from informal (mean = 97.1 μg/kg) than formal (mean = 55.5 μg/kg) market outlets. There was a positive and sig- nificant correlation (R2 = 0.63; p ≤ 0.05) between aflatoxin levels and the major aflatoxin producing fungi in raw pea- nuts from formal markets in Eldoret town. Additionally, total aflatoxin in raw peanut samples from informal markets in Kericho was positively and significantly correlated (R2 = 0.81; p ≤ 0.05) to the population of A. flavus (L and S strains). In roasted coated peanuts sampled from formal market outlets in Eldoret, aflatoxin levels correlated positively and sig- nificantly (R2 = 0.37; p ≤ 0.05) with A. flavus S strain. There is need to create awareness among peanut traders and con- sumers on proper handling of peanuts and health risks associated with consumption of unsafe peanut products.